(untitled) - Ng, Deborah (Hoboken, N.J., 2012)
This straightforward-but-fun guide shows you how to effectively manage, grow, and communicate with your online community. Clear coverage shares tips for dealing with customers and fans through Twitter, Facebook, forums, and blogs.
Keywords: Marketing,Online social networks,Tiếp thị qua mạng,Tiếp thị,Mạng xã hội trực tuyến,Internet marketing; Management,Management,Quản lý,Quản lý